Legal Analysis of Child Adoption: An Islamic Perspective and Implementation in Religious Courts - Hasbiyalla, Iklil (STAI Miftahul Ula Nganjuk, 2025)
Child adoption is a practice that has long been known in society, both in the perspective of Islamic law and positive law in Indonesia. This research discusses the procedure of child adoption in the Religious Court, the legal basis that regulates it, as well as the legal implications for adopted children and adoptive parents. In Islam, child adoption is allowed provided that the child's nasab status remains with his or her biological parents, as explained in the Qur'an and Hadith. Meanwhile, in Indonesian positive law, child adoption is regulated in various regulations, such as Law Number 23 of 2002 concerning Child Protection, as well as the Compilation of Islamic Law (KHI). This research uses a qualitative method with a descriptive-analytical approach to describe and compare the provisions of child adoption in the perspective of Islam and state law. The results show that although there are differences in concepts between Islamic law and positive law, both aim to protect the rights of children so that they can grow and develop properly. In addition, the process of child adoption in the Religious Court aims to provide legal certainty for adopted children and adoptive parents. Therefore, a comprehensive understanding of the procedures and legal consequences of child adoption is essential for the community to avoid mistakes in its implementation.